A Systematic Literature Review of Three Modalities in Technologically Assisted TKA - William A. Leone; Leah C. Elson; Christopher R. Anderson (Advances in Orthopedics)
In effort to reduce the revision burden of total knee arthroplasty (TKA), industry emphasis has focused on replacing manual techniques—which are subject to variability—with technological implements. Unfortunately, technological innovation often continues before adequate time for critical evaluation has passed. Therefore, the purpose of this descriptive literature review was to collect a large sample of international data and report on the clinical and economic efficacy of three major types of technologically assisted TKA: navigation, patient-specific instrumentation, and sensorized trials.